Environmental quality perception and management in industries in Ondo state, Nigeria - Afolabi Francis Fatusin (Economic and Environmental Studies (E&ES), 2015)
There is a direct correlation between the state of environment and environmental quality perception of individuals residing in the geographical entity. This study, working on the assumption that the more the awareness of quality environment the more the tendency to improve it examined the perception of entrepreneurs of industries and residents on the state of environmental management among 200 industries in Ondo state and 172 residents living within 100 meter radius to the sampled industries who were interviewed with different sets of questionnaire. Data collected were analysed using tables and charts. The mean weighted value (MWV) of each category of responses was compared with the group mean weighted value (GMWV) to isolate the most important responses. The study discovered that majority of proprietors, being lowly educated disposed wastes using crude means like burning (57%), burying (23%), disposing in the bush. (12%) and in drainages (11%). Out of the 200 residents sampled majority 87.2% (191) believed they were injuriously affected by the operation of adjoining factories. Moreover there existed a discrepancy of opinion among proprietors and people living nearby on the assessment of environmental management technique adopted in managing wastes. The paper posited that poor judgment by proprietors, inertia by government supervisory agencies, dirty attitudes of people and poor education among proprietors were the most important responses of people on reasons for poor state of waste management. The paper concluded that right perception of the problem through improved environmental education is essential for sustainable solution to wastes management in industries.
Keywords: Y; 330; Environmental Management; Wastes; Industries; Proprietors; Perception; Environmental quality